Income analysis of cocoa farming in Punduh Pidada District, Pesawaran Regency - Duana, Resi; Situmorang, Suriaty; Saleh, Yuliana (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2024)
This study aims to analyze cocoa farming income and post-harvest processing in post-harvest processing in Punduh Pidada Sub-district, Pesawaran Regency. This research uses survey method by conducting interviews to 53 sample farmers in 2 villages, namely 29 farmers in Baturaja Village and 24 farmers in Banding Agung Village. 24 farmers in Banding Agung Village. Sample determination was carried out with a simple random sampling technique. technique (simple random sampling) and data collection using a questionnaire. Data collection was conducted in February to March 2023. This research data was analyzed by using income analysis according to Soekartawi. Results fresh cocoa farming income obtained by farmers in Punduh Pidada Subdistrict of Pesawaran Regency is IDR23.992.537,37/ha/year. Whereas cocoa farming income with drying (post-harvest management) is 1, 2, 3, and 4 days drying respectively amounted to IDR40,949,018.88/ha/year, IDR38,870,452/ha/year, IDR29,485,659.01/ha/year, and IDR16,345,331.58/ha/year. R/C has a result of more than 1, meaning that cocoa farming is profitable and feasible to cultivate.